Climacteric symptoms and quality of life: validity of women's health questionnaire - Silva Filho, Carlos Rodrigues da; Baracat, Edmundo Chad; Conterno, Lucieni de Oliveira; Haidar, Mauro Abi; Ferraz, Marcos Bosi (Revista de Saúde Pública, 2005)
OBJECTIVE: To evaluate the reliability and validity of the Portuguese version of the Women's Health Questionnaire. METHODS: In order to evaluate the Women's Health Questionnaire (WHQ), an analytical cross-sectional study was carried out at the women's menopause outpatient clinic of a university hospital in São Paulo, Brazil. There were studied 87 women in perimenopause or menopause, defined as experiencing at least one year's absence of menstrual flow. The following variables were collected: demographic data, clinical variables (Kupperman index and correlate numeric scale) and quality of life indexes (SF-36 and utility). RESULTS: The WHQ proved to be a questionnaire easily translated into Portuguese and well-adjusted to Brazilian women. The internal consistency of the overall WHQ was excellent (Cronbach alpha =0.83; 95% CI: 0.71-0.91). Test-retest reliability was also excellent (intraclass correlation coefficient [ICC]=0.92; 95% IC: 0.86-0.96) and had good absolute agreement (0.84; 95% CI: 0.71-0.92). A satisfactory clinical validity was observed. The construct validity was corroborated by clear associations with others scales. A good index of responsiveness after the intervention was reached. CONCLUSIONS: The Portuguese version of the WHQ is of easy and fast administration and understanding. Its measuring properties were related, allowing its use in the evaluation of Brazilian climacteric women's quality of life for various purposes.